Eplerenone Implantation Improved Adipose Dysfunction Averting RAAS Activation and Cell Division - Vecchiola, Andrea; Fuentes, Cristóbal A.; Solar, Isidora; Lagos, Carlos F.; Opazo, Maria Cecilia; Muñoz-Durango, Natalia; Riedel, Claudia A.; Owen, Gareth I.; Kalergis, Alexis M.; Fardella, Carlos E. (Frontiers in Endocrinology, 2020)
Mineralocorticoid receptor (MR) activation within adipose tissue, triggers inflammation and metabolic syndrome development. The pharmacological blockade of MR provides beneficial effects for adipose tissue. Our study evaluates the impact of eplerenone implantation upon obesity. Experimental Approach: Mice with implanted placebo pellets were fed a normal diet (ND) or a high fat diet (HFD). Additionally, a group of mice fed HFD were implanted with an eplerenone pellet. Metabolic and biochemical parameters were assessed in each animal group. Adipocyte size and lipid accumulation were investigated in the liver and adipose tissue. The local renin-angiotensin-aldosterone system (RAAS) components were evaluated in adipose tissue. Key Results: Eplerenone reduced HFD-induced body weight gain, fasting glucose levels, fat accumulation, HFD-induced adipocyte size and liver lipid accumulation and improved glucose tolerance. In the adipose tissue, HFD significantly increased the mRNA levels of the RAAS molecules relative to the ND group. Eplerenone lowered RAAS mRNA levels, components of lipid metabolism and markers of inflammation in HFD-fed animals. Conclusion: MR antagonism with eplerenone attenuates obesity-related insulin resistance partly through reduction of RAAS activation, inflammatory progression and the induction of cytokines. This suggests that eplerenone should be further studied as a therapeutic option for obesity and overweight.